Bagaimana price perception, brand image, dan service quality mempengaruhi consumer buying interest?: Empirical study - Mutmainah, Mutmainah; Nikmah, Masfi'atun (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2023)
This study aims to determine the effect of price perception, brand image, service quality on purchase intention at umammi cheese banana outlets in Mojokerto City either partially or simultaneously. The research method used is a quantitative research method with descriptive analysis and data sources, namely primary data and secondary data. The population in this study are consumers who buy cheese bananas whose population is known, namely 85 samples. The data analysis technique used is multiple linear regression. The test results with regression analysis found that price perception, brand image, and service quality have a partial effect on consumer buying interest. Simultaneously, price perception, brand image, and service quality also influence consumer buying interest. The novelty of this study is that we jointly test how the correlation of price perception, brand image, service quality in encouraging consumer buying interest, which previously was rarely done by many studies.